2016
DOI: 10.1055/s-0042-112588
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic retention of the patency capsule: a multicenter real life case series

Abstract: Background and aims: The patency capsule is designed to evaluate the patency of the small bowel before administration of small-bowel capsule endoscopy (SBCE) in patients at high risk of retention. The utilization of a patency capsule may be associated with a risk of symptomatic retention, but very few cases have been reported to date. The aim of our study was to describe our experience with this rare complication of a patency capsule. Methods: This was a multicenter retrospective case series. The medical recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…This disease location is frequently underestimated during the initial assessment; nevertheless, CE may detect active inflammation in the jejunum or proximal ileum in over 50% of patients with established CD [35]. The currently accepted Montreal classification does not specifically address proximal SB disease location [36], which is better reflected in the pediatric Paris classification (L4b) [37]. The assessment of disease severity and extent is essential for diagnostic categorization and management planning in pediatric inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…This disease location is frequently underestimated during the initial assessment; nevertheless, CE may detect active inflammation in the jejunum or proximal ileum in over 50% of patients with established CD [35]. The currently accepted Montreal classification does not specifically address proximal SB disease location [36], which is better reflected in the pediatric Paris classification (L4b) [37]. The assessment of disease severity and extent is essential for diagnostic categorization and management planning in pediatric inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings con rm that performing an initial PCE before VCE in patients with a high-risk of retention, represented by the known IBD, is useful to avoid retention [40,41]. It is noteworthy that not all patients undergoing VCE should be offered a patency capsule since several complications have been reported, including small bowel obstruction [42] and perforation [43]. Surgery is frequently performed for retained capsules in the early years [44]; however, for asymptomatic patients or with slight abdominal pain, later studies reported more favorable clinical outcomes using endoscopic methods or medical treatment [45,46].…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, newer second-generation patency capsule designs include an RFID tag and two timer plugs at each end to allow for easier penetration of the intestinal fluid. Kopylov et al [ 10 ] reported 20 symptomatic cases of retention out of 1,615 second-generation patency capsule tests, with only 1 case requiring surgery. They also collected case series from the literature pertaining to the use of first- and second-generation patency capsules [ 10 ].…”
Section: Discussionmentioning
confidence: 99%